Slow + Fashion – Women's Wisdom. (2nd September 2019) - Clark, Hazel
Abstract: Building on ideas I first published in 2008 as, "Slow + Fashion - An Oxymoron or a Promise for the Future…?", this paper brings new insights to the value of a slow approach to fashion. The cases explored for that research indicated the significant role of women practitioners. As a consequence, further investigation and thinking leads me to propose here a development of the slow + fashion discourse that respects and is informed by feminine strategies and values, or what I am choosing to call women's wisdom. In this paper, the work of women thinkers, scholars and design professionals is discussed to explore the potential of developing further the "+" of slow + fashion and to draw from and value the long-established existence of beliefs and methods common to women that can also pre-date and transcend capitalism, modernity, and Eurocentricity, and which are not formed on the basis of patriarchy. Attention is drawn to everyday values, history, sensory studies, micro-phenomenology, and fashion design practices that indicate the potential for a system change in fashion. Implicit is a shift in worldview to challenge the fashion status quo, and to introduce different economic logic, business models, values and processes than those that currently dominate the fashion system. The paper demonstrates that models already exist in theories and practices which have been devised and applied by women. It concludes that women's wisdom added to a slow + fashion can contribute to establishing much needed sets of principles to move us forward and change perspectives.